CORRELATION OF BODY MASS INDEX (BMI) AS A MODIFIABLE RISK FACTOR IN DIABETIC FOOT ULCER FORMATION. A VALIDATION STUDY (Journal of Medical & Health Sciences Review, 2025)
Objectives: To analyze the effect of weight gain and obesity on the characteristics of diabetic foot ulcer along with associated complications and outcomes.Study Design: Analytical (Observational)Setting: Department of medicine/surgery, Khyber Teaching Hospital, Peshawar.Duration: From 1st July 2024 to 31st December 2024.Methodology: After attaining approval from the hospital ethical and research committee, the following study began with a sample size of 125 patients, all added through non-probability consecutive sampling technique. The following parameters were considered: age, gender, education, MR number, contact number, locality, duration of T2DM, outcomes, complications, characteristics of the ulcer and the BMI. The data was added to Microsoft Excell and transferred to SPSS version23.0 for data analysis. Pearson chi-square test was utilized to measure correlation and regression. Results are shown in the form of description, tables and charts.Results: Out of 125 patients recruited for the study, 32 (25.4%) were females and 94 (74.6%) patients were males with a mean age of 57.8 ± 0.617. Patients who were not obese had healthier margins (p value = 0.04), better outcomes (p value= 0.05) and had the ulcer for a lesser duration of time (p-value 0.016) as compared to their counterparts. Exactly 23 (18.4%) patients, who were obese, had to undergo either toe or trans-metatarsal/midtarsal amputation.Conclusion: Obesity has a negative impact on wound healing through pressure effects and compromised circulation hence leading to the formation of diabetic foot ulcers with poor outcomes.